164k views
2 votes
Find the difference between x+5 and 2x+3

User Irregular
by
4.8k points

2 Answers

5 votes


(2x + 3) - (x + 5) = 2x + 3 - x - 5 =x - 2
User Namuna
by
5.7k points
5 votes

Answer:

The difference between the given expressions would be
x - 2

Explanation:

Given phrase,

Difference between x+5 and 2x+3,


( 2x + 3 ) - (x + 5)


=2x + 3 - x - 5 ( By distributive property )


=x - 2 ( By combining like terms )

Hence, the required difference would be
x-2

User Mr Teeth
by
5.1k points